The incidence and differential diagnosis of acute groin injuries in male soccer players - Ekstrand, J.; Hilding, J. (Scandinavian Journal of Medicine & Science in Sports, 1999)
This prospective cohort study evaluated the incidence of acute groin injuries and estimated the distribution of differential diagnoses in male soccer players. Two senior male soccer divisions (21 teams, 326 players) were followed for 1 year. Patients with groin injuries were examined clinically as well as by herniography, sonography and by plain x-ray of the pelvic bones. Groin injuries accounted for 8% of all injuries. The incidence of groin injury was 0.8/1000 h of exposure. Thirteen (52%) of the 25 patients were clinically considered to have a muscle/tendon injury. However, when using sonography, muscle/tendon injury was only verified in 1 patient. Clinical suspicion of hernia or incipient hernia was evident in 4 (16%) of the patients, while 14 (56%) had a pathological finding at herniography. Clinical and paraclinical (i.e. diagnostic methods using imaging and other advanced techniques) diagnoses do not correspond very well in acute groin injury. Scand J Med Sci Sports 1999 Apr;9(2):98-103